2012
DOI: 10.3111/13696998.2012.751918
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug treatment patterns and economic burden of commercially-insured patients with refractory epilepsy with partial onset seizures in the United States

Abstract: Pattern of use was very dynamic, suggesting seizures are not well-controlled. Improving seizure control and reducing economic burden of refractory epilepsy remain important unmet medical needs in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 22 publications
2
61
1
Order By: Relevance
“…Contrary to the findings in the overall population, for children receiving their initial prescription for epilepsy, monotherapy was used in about 83.9 % of cases and valproic acid was the most widely used AED, findings that are consistent with the previous report and guideline [27].…”
Section: Monotherapy Versus Polytherapycontrasting
confidence: 60%
See 1 more Smart Citation
“…Contrary to the findings in the overall population, for children receiving their initial prescription for epilepsy, monotherapy was used in about 83.9 % of cases and valproic acid was the most widely used AED, findings that are consistent with the previous report and guideline [27].…”
Section: Monotherapy Versus Polytherapycontrasting
confidence: 60%
“…Although levetiracetam is a popular AED in adult patients [27] and its efficacy in the initial monotherapy for patients aged 12 years was demonstrated to be comparable to lamotrigine [28], a low usage of levetiracetam was observed in this study. Its late introduction in Korea and restricted indications for pediatric epilepsy might explain this low usage.…”
Section: Utilization Of Individual Aedsmentioning
confidence: 59%
“…Annual total costs of drug-resistant epilepsy in the United States approach $4 billion, with average annual health-care costs for a patient with drug-resistant seizures (defined as those on ≥3 AEDs) at $33,613 [10]. Patient benefit in the current analyses was evident not only through traditional measures of seizure frequency but also on the CGI-C, which indicated that clinicians deemed patient status significantly improved with USL255 relative to placebo.…”
Section: Discussionmentioning
confidence: 65%
“…The specific definitions we chose for patients having "highly drugresistant" seizures (≥2 concurrent AEDs and ≥4 lifetime AEDs) or patients having "less drug-resistant" seizures (1 concurrent AED or b 4 lifetime AEDs) were based on our clinical experience as well as a recent pharmacoeconomic study that classified 'refractory patients' as those on 3 or more AEDs [10]. Our analysis investigates an important group of patients with ILAE-defined "treatment failure."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation